Latinx Immigrants Transcending Acculturation and Xenophobia (International and Cultural Psychology, 2018)
This richly detailed reference offers a strengths-based survey of Latinx immigrant experience in the United States. Spanning eleven countries across the Americas and the Caribbean, the book uses a psychohistorical approach using the words of immigrants at different processes and stages of acculturation and acceptance. Coverage emphasizes the sociopolitical contexts, particularly in relation to the US, that typically lead to immigration, the vital role of the Spanish language and cultural values, and the journey of identity as it evolves throughout the creation of a new life in a new and sometimes hostile country. This vivid material is especially useful to therapists working with Latinx clients reconciling current and past experience, coping with prejudice and other ongoing challenges, or dealing with trauma and loss. Included among the topics: · Argentines in the U.S.: migration and continuity. · Chilean Americans: a micro cultural Latinx group. · Cuban Americans: freedom, hope, endurance, and the American Dream. · The drums are calling: race, nation, and the complex history of Dominicans. · The Obstacle is the Way: resilience in the lives of Salvadoran immigrants in the U.S. · Cultura y familia: strengthening Mexican heritage families. · Puerto Ricans on the U.S. mainland. With its multiple layers of lived experience and historical analysis, Latinx Immigrant, is inspiring and powerful reading for sociologists, economists, mental health educators and practitioners, and healthcare providers.